IDENTIFICATION OF EARTHQUAKE AND TSUNAMI RISK ZONES IN SOUTHERN JAVA USING GRAVITY METHOD - Karima, Isna; Martha, Agustya Adi; Hudayat, Nurul; Zera, Tati (Marine Geological Institute of Indonesia, 2025)
The southern part of Java has a high level of disaster risk because it is affected by a subduction zone where the Indo-Australian plate thrusts beneath the Eurasian plate. Six tsunami events occurred in the southern part of Java, caused by earthquakes in the area, based on BMKG catalogue data from 416 to 2023. Given the very large population on the island of Java, the possibility of causing more casualties is greater. Therefore, it is very necessary to have thorough mitigation preparation to estimate the possibility of areas experiencing a large earthquake that triggers a tsunami. This study aims to determine areas with a high level of earthquake and tsunami risk distribution using the gravity method with data from the TOPEX satellite in the form of free air anomaly data and topographic data. After data processing and an anomaly map were obtained, it showed that areas with a high level of earthquake risk were located around the subduction zone and Java Trench. This is due to the geological conditions of the southern part of Java, located in the subduction zone where many active faults were found.